2009
DOI: 10.1111/j.1747-0765.2009.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous rice straw compost application on rice yield and soil properties in the Mekong Delta

Abstract: A field experiment was conducted to study the effects on yield and soil properties of the continuous application of rice straw compost to an alluvial soil in the Mekong Delta, Vietnam. Fourteen rice crops, two crops per year, were grown by direct seeding of the crop. There were seven treatments: F0C) (no fertilizer and compost), F0C+ (compost with no fertilizer), F20C+, F40C+, F60C+, F80C+ (20, 40, 60 and 80% of the fertilizer application rate with compost, respectively), F100C) (full strength fertilizer appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
3
16
0
2
Order By: Relevance
“…4) but were not correlated with the yield increase. These results are in accordance with those of previous studies 20 . The concentrations of K, Ca, Mn, Fe, Zn, and Cu did not differ significantly among treatments ( Table 3), suggesting that these elements may not be limiting factors for the rice yield.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…4) but were not correlated with the yield increase. These results are in accordance with those of previous studies 20 . The concentrations of K, Ca, Mn, Fe, Zn, and Cu did not differ significantly among treatments ( Table 3), suggesting that these elements may not be limiting factors for the rice yield.…”
Section: Discussionsupporting
confidence: 83%
“…The results of our present study contradict this conclusion. Watanabe et al 20 reported the significant effect of RSC application on soil physical properties. RSC application was shown to maintain soils in a softer state, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations